Manganese-zinc ferrite with ultra-wide temperature, wide magnetic conductivity and low loss as well as preparation method and application of manganese-zinc ferrite

By using a combination of more Fe2O3 and less ZnO formulations and auxiliary components in magnetic materials, ultra-wide temperature, wide magnetic permeability, low loss manganese zinc with low power consumption and high saturation flux density in the range of -40°C to 160°C was prepared. Ferrite solves the problem of rapid increase in high temperature losses of existing materials and is suitable for automotive electronics and photovoltaic inverters.

CN119143495AActive Publication Date: 2024-12-17广东尚朋电磁科技有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411484264.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-17
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The loss of existing magnetic materials increases rapidly after the temperature range exceeds 140℃, and cannot maintain excellent loss and saturated flux density characteristics within the range of -40℃ to 160℃, and cannot meet the passive devices of automotive electronics and photovoltaic inverters. Strict temperature requirements.

Method used

Using the formula of more Fe2O3 and less ZnO, combined with CaCO3, TiO2, Nb2O5, Co3O4 and SnO2 as auxiliary components, ultra-wide temperature, wide magnetic permeability, low loss manganese zeolite is prepared through ball mill mixing, pre-sintering and other steps to control it. Grain growth and microstructure reduce sintering temperature and improve the wide temperature performance of the material.

Benefits of technology

Low power consumption in the range of -40°C to 160°C, high saturation flux density, initial permeability of 3000, suitable for automotive electronics and photovoltaic inverters, providing a wider application temperature range and higher permeability .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143495A_ABST
    Figure CN119143495A_ABST
Patent Text Reader

Abstract

The invention discloses manganese zinc ferrite with ultra-wide temperature width magnetic conductivity and low loss as well as a preparation method and application thereof, and belongs to the technical field of magnetic materials. By adopting the formula of more Fe2O3 and less ZnO, the magnetocrystalline anisotropy constant K1 and the saturation magnetostriction coefficient lambda s are reduced, the saturation magnetization Ms is increased, the internal and external stress of the material is reduced, an accurate and uniform microstructure is formed, and the magnetic material with high initial permeability, high saturation magnetic flux density and ultralow power consumption can be obtained; caCO3, TiO2, Nb2O5, Co3O4 and SnO2 are introduced as auxiliary components, the auxiliary components can enter crystal grains and crystal boundaries, solid-phase reaction is promoted, the sintering temperature is reduced, crystal grain growth is controlled, the ultra-wide-temperature-width magnetic conductivity of the manganese-zinc ferrite is improved, the obtained manganese-zinc ferrite with the ultra-wide-temperature-width magnetic conductivity and low loss has wide temperature and ultra-low power consumption, and the application temperature range is from-40 DEG C to 160 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnetic materials, and in particular relates to an ultra-wide temperature range, low-loss manganese-zinc ferrite with magnetic permeability, and a preparation method and application thereof. Background Art

[0002] Due to factors such as location and power, automotive electronics and photovoltaic inverters have very stringent temperature requirements for passive components. In particular, transformers and inductors, which are the main components, have very high temperature characteristics, requiring materials to have ultra-wide temperature characteristics, specifically requiring materials to have excellent and stable characteristics from -40°C to 160°C.

[0003] In recent years, technical personnel in the industry have done a lot of research to obtain wide-temperature ultra-low power consumption magnetic materials. For example, patent CN202111420511.5 discloses a wide-temperature, low-loss, high-strength MnZn power ferrite and its preparation method and application. Under the conditions of 100kHz and 200mT, the power consumption of this material at 25℃ is ≤350mW / cm 3 , 120℃ power consumption ≤350mW / cm 3 ; Under the conditions of 1194A / m and 50Hz, the saturation magnetic flux density at 25℃ is ≥535mT, and the material has excellent loss and saturation magnetic flux density characteristics at 25℃ to 120℃. For example, patent CN202310829822.X discloses a wide temperature, low-loss soft magnetic manganese-zinc ferrite material suitable for 25-140℃ and its preparation method and application. The material has excellent loss and saturation magnetic flux density characteristics at 25℃ to 140℃, and can also better meet the requirements of vehicle-mounted OBC and DC-DC. However, the temperature that the above two materials can meet is limited to the range of 25℃ to 140℃ at normal temperature, and the wide temperature, low-loss soft magnetic manganese-zinc ferrite material disclosed in patent CN202310829822.X has a rapid increase in loss and deterioration after the temperature exceeds 140℃.

[0004] Therefore, there is an urgent need for a magnetic material having excellent loss and saturation flux density characteristics at -40°C to 160°C to solve the above problems. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes an ultra-wide temperature and permeability low-loss manganese-zinc ferrite and its preparation method and application. The ultra-wide temperature and permeability low-loss manganese-zinc ferrite provided by the present invention has a wide temperature and ultra-low power consumption, and the application temperature range is from -40°C to 160°C, and also has very high saturation flux density and permeability.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides an ultra-wide temperature range, low-loss manganese-zinc ferrite with magnetic permeability, including a main component and auxiliary materials;

[0008] In terms of molar percentage, the main components include Fe 2 O 3 53.48-53.78mol%, ZnO 10.25-10.50mol% and the balance MnO;

[0009] The auxiliary material includes CaCO 3 、TiO 2 , Nb 2 O 5 、Co 3 O 4 and SnO 2 .

[0010] Preferably, based on the total weight of the main components, the auxiliary materials include CaCO 3 0.02-0.04%, TiO 2 0.1-0.4%, Nb 2 O 5 0.02-0.03%、Co 3 O 4 0.3-0.5% SnO 2 0.1-0.3%.

[0011] The present invention provides a method for preparing the ultra-wide temperature range and low-loss manganese-zinc ferrite according to the above technical solution, comprising the following steps:

[0012] (1) Weigh Fe by mole percentage 2 O 3 , ZnO and MnO, and then ball-milling and pre-calcining to obtain a pre-calcined material;

[0013] (2) Weighing each auxiliary material according to the total weight of the main component, then ball-milling the auxiliary material and the pre-sintered material obtained in step (1), pressing and sintering to obtain the ultra-wide temperature range and low-loss manganese-zinc ferrite.

[0014] Preferably, in step (1), the material-water ratio of the ball milling mixture is 1:(1.1-1.2), the material-ball ratio is 1:(3-4), the grinding balls are steel balls with a diameter of ф=3 mm, and the grinding time is 60-80 min.

[0015] Preferably, in step (1), the pre-calcination temperature is 930-960° C., the feed rate is 2-4 kg / h; and the spinel synthesis degree of the pre-calcined material is 30-40%.

[0016] Preferably, in step (2), the material-water ratio of the ball milling mixture is 1:(1-1.2), the material-ball ratio is 1:(5-6), the grinding balls are steel balls with a diameter of ф=3 mm, and the grinding time is 70-90 min.

[0017] Preferably, in step (2), zinc stearate is added during the compression molding process; the amount of zinc stearate added is 2-3‰.

[0018] Preferably, in step (2), the sintering includes a heating stage, a heat preservation stage and a cooling stage.

[0019] Preferably, the heating stage is: in an air atmosphere, the temperature is raised from room temperature to 1260-1300°C, and the heating time is 6-8h; the insulation stage is: insulation for 5-6h at 1260-1300°C and an oxygen content of 2-3%; the cooling stage is: in a reducing atmosphere, the temperature is cooled from 1260-1300°C to room temperature at a rate of 3-4°C / min.

[0020] The present invention also provides the use of the ultra-wide temperature range, permeability and low-loss manganese-zinc ferrite described in the above technical solution in a transformer or inductor.

[0021] Compared with the prior art, the present invention has the following advantages and technical effects:

[0022] The present invention adopts multi-Fe 2 O 3 , less ZnO formula, reduce the magnetocrystalline anisotropy constant K 1 and saturation magnetostriction coefficient λ s , increase the saturation magnetization Ms, reduce the internal and external stress of the material, form a precise and uniform microstructure, and obtain magnetic materials with high initial permeability, high saturation flux density, and ultra-low power consumption; by introducing CaCO 3 、TiO 2 , Nb 2 O 5 、Co 3 O 4 and SnO 2 As an auxiliary component, the auxiliary component can enter the interior of the grains and the grain boundaries, promote solid phase reaction, reduce the sintering temperature, control grain growth, and help improve the wide temperature and wide permeability of manganese-zinc ferrite.

[0023] The ultra-wide temperature and permeability low-loss manganese-zinc ferrite provided by the present invention has a power consumption of ≤400mW / cm2 at -40°C under the conditions of 100kHz and 200mT. 3 , 160℃ power consumption ≤400mW / cm 3; Under the conditions of 1194A / m and 50Hz, the saturation flux density at 25℃ is ≥550mT, the saturation flux density at 140℃ is ≥410mT, and the initial magnetic permeability is 3000. Compared with existing magnetic materials, it has lower power consumption over a wider temperature range, a wider application temperature range from -40℃ to 160℃, higher saturation flux density and magnetic permeability, and is very suitable for applications in automotive electronics and photovoltaics. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0025] Figure 1 The figure is a curve diagram showing the power consumption of the manganese-zinc ferrite in Example 2 and Comparative Example 1 as a function of temperature. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] The embodiment of the present invention provides an ultra-wide temperature range and low-loss manganese-zinc ferrite with magnetic permeability, including a main component and auxiliary materials;

[0029] In terms of molar percentage, the main components include Fe 2 O 3 53.48-53.78mol%, ZnO 10.25-10.50mol% and the balance MnO;

[0030] The auxiliary material includes CaCO 3 、TiO 2 , Nb 2 O 5 、Co 3 O 4 and SnO 2 .

[0031] In a preferred embodiment, the main component includes Fe 2 O 353.48-53.58mol%, ZnO 10.25-10.30mol% and the balance MnO. 2 O 3 , less ZnO formula, reduce the magnetocrystalline anisotropy constant K 1 and saturation magnetostriction coefficient λ s , increase the saturation magnetization intensity Ms, reduce the internal and external stress of the material, form a precise and uniform microstructure, and obtain magnetic materials with high initial magnetic permeability, high saturation magnetic flux density, and ultra-low power consumption.

[0032] In a preferred embodiment, based on the total weight of the main components, the auxiliary materials include CaCO 3 0.02-0.04%, TiO 2 0.1-0.4%, Nb 2 O 5 0.02-0.03%、Co 3 O 4 0.3-0.5% SnO 2 0.1-0.3%. The present invention introduces CaCO 3 、TiO 2 , Nb 2 O 5 、Co 3 O 4 and SnO 2 As an auxiliary component, the auxiliary component can enter the interior of the grain and the grain boundary, promote the solid phase reaction, reduce the sintering temperature, control the grain growth, and help improve the wide temperature and wide permeability of the manganese-zinc ferrite; the introduction of the auxiliary component can control the internal grain size to be above 12μm and the external grain size to be below 12μm. 2 With Co 3 O 4 After the combination, the magnetocrystalline anisotropy constant K 1 Zero, which helps to reduce the high temperature power consumption of manganese zinc ferrite, SnO 2 The addition of Fe 3+ Transformed into Fe 2+ The effect is helpful to reduce the low-temperature power consumption of manganese-zinc ferrite.

[0033] The present invention provides a method for preparing the ultra-wide temperature range and low-loss manganese-zinc ferrite according to the above technical solution, comprising the following steps:

[0034] (1) Weigh Fe by mole percentage 2 O 3 , ZnO and MnO, and then ball-milling and pre-calcining to obtain a pre-calcined material;

[0035] (2) Weighing each auxiliary material according to the total weight of the main component, then ball-milling the auxiliary material and the pre-sintered material obtained in step (1), pressing and sintering to obtain the ultra-wide temperature range and low-loss manganese-zinc ferrite.

[0036] In a preferred embodiment, in step (1), the material-water ratio of the ball milling mixture is 1:(1.1-1.2), the material-ball ratio is 1:(3-4), the grinding balls are steel balls with a diameter of ф=3 mm, and the grinding time is 60-80 min; the average particle size of the slurry obtained by the ball milling mixture is 1.10-1.20 μm.

[0037] In a preferred embodiment, in step (1), the pre-burning temperature is 930-960°C, and the feed rate is 2-4kg / h. The present invention controls the pre-burning temperature and feed rate within the above range, which is conducive to ensuring and stabilizing the spinel synthesis degree. Changing the pre-burning temperature will change the magnetization of the powder, thereby changing the density of the manganese-zinc ferrite, and ultimately changing the power consumption.

[0038] In a preferred embodiment, in step (1), the pre-firing is carried out under air conditions; the pre-firing equipment is a natural gas 500 type rotary kiln; and the rotation speed of the natural gas 500 type rotary kiln is 2N / min.

[0039] In a preferred embodiment, in step (1), the spinel synthesis degree of the pre-sintered material is 30-40%.

[0040] In a preferred embodiment, in step (2), the material-water ratio of the ball milling mixture is 1:(1-1.2), the material-ball ratio is 1:(5-6), the grinding balls are steel balls with a diameter of ф=3 mm, and the time is 70-90 min; the average particle size of the slurry obtained by the ball milling mixture is 1.00-1.10 μm.

[0041] In a preferred embodiment, in step (2), the ball milling mixing further includes mixing the slurry obtained by the ball milling mixing with a PVA solution; the concentration of the PVA solution is 8%, and the amount used is 10% of the slurry mass; the mixing method is stirring, the stirring time is 120 minutes, and the rotation speed is 175rpm.

[0042] In a preferred embodiment, in step (2), zinc stearate is added during the pressing process; the amount of zinc stearate added is 2-3‰; the density of the standard green body obtained by pressing is controlled at 3g / cm 3 .

[0043] In a preferred embodiment, in step (2), the sintering includes a heating stage, a heat preservation stage and a cooling stage.

[0044] In a preferred embodiment, the heating stage is: heating from room temperature to 1260-1300°C in air atmosphere, and the heating time is 6-8h; the heat preservation stage is: heat preservation at 1260-1300°C and oxygen content of 2-3% for 5-6h; the cooling stage is: cooling from 1260-1300°C to room temperature at a rate of 3-4°C / min in a partially reducing atmosphere. The cooling stage of the present invention is carried out in a partially reducing atmosphere, so that the wide temperature and low loss performance of the material is greatly improved.

[0045] In a preferred embodiment, the partially reducing atmosphere follows the Morin Liu formula log0 2 % = ab / T (where a and b are empirical constants. In manganese-zinc ferrite, a is usually about 7, b is usually about 14540, and T is the sintering temperature / K). In the present invention, a is preferably 6.2-6.5. In the cooling stage, when the oxygen content setting value is lower than the calculated value of the formula, it is a reducing atmosphere. The manganese-zinc ferrite undergoes a reduction reaction, and Fe 3+ Converted to Fe 2+ When the oxygen content setting value is higher than the value calculated by the formula, it is an oxidizing atmosphere and an oxidation reaction occurs; when the oxygen content setting value is the same as the value calculated by the formula, it is a balanced atmosphere and no chemical reaction occurs.

[0046] The present invention also provides the use of the ultra-wide temperature range, permeability and low-loss manganese-zinc ferrite described in the above technical solution in a transformer or inductor.

[0047] The room temperature in the embodiments of the present invention refers to "25±2°C".

[0048] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.

[0049] Examples 1-2 and Comparative Example 1

[0050] A method for preparing ultra-wide temperature and permeability low-loss manganese-zinc ferrite:

[0051] (1) Weigh Fe by mole percentage 2 O 3 , ZnO and MnO, and then ball-milled and mixed, the material-water ratio of ball milling was 1:1.1, the material-ball ratio was 1:3, the grinding balls were ф=3mm steel balls, the ball milling time was 60min, and a slurry with an average particle size of 1.1μm was obtained.

[0052] (2) The slurry obtained in step (1) is pre-fired in air using a natural gas 500 type rotary kiln to obtain a pre-fired material with a spinel synthesis degree of 32%; wherein the rotation speed of the natural gas 500 type rotary kiln is 2N / min, the pre-fired temperature is 945°C, and the feed rate is 4kg / h.

[0053] (3) Weigh each auxiliary material according to the total weight of the main component, and then ball-mill the auxiliary material and the pre-sintered material obtained in step (1), wherein the material-water ratio of the ball milling is 1:1, the material-ball ratio is 1:5, the grinding ball is a steel ball with a diameter of ф=3 mm, and the ball milling time is 70 min to obtain a slurry with an average particle size of 1.10 μm, and then add a PVA solution (concentration of 8%) of 10% by mass of the slurry and stir at a speed of 175 rpm for 120 min, then add zinc stearate at an addition amount of 2‰, and then press-form to obtain a slurry with a density of 3 g / cm 3 of the green body.

[0054] (4) Sintering the green body obtained in step (3), heating stage: heating from room temperature to 1260° C. in air atmosphere, heating time 6 hours, constant heating rate; holding stage: holding at 1260° C., oxygen content 2%, for 5 hours; cooling stage: cooling from 1260° C. to room temperature at a rate of 3° C. / min in a partially reducing atmosphere, to obtain ultra-wide temperature range, low-loss manganese-zinc ferrite; wherein the partially reducing atmosphere follows the Morin Liu formula logO 2 %=ab / T, a is 6.2-6.5.

[0055] The ingredients and properties of Examples 1-2 and Comparative Example 1 are shown in Table 1.

[0056] Table 1 Composition and performance of Examples 1-2 and Comparative Example 1

[0057]

[0058] It can be seen from Table 1 that the ultra-wide temperature and permeability low-loss manganese-zinc ferrite in Example 1 and Example 2 has a wider temperature range and low power consumption. In the range of -40°C to 160°C, the power consumption is low and does not change much. 3 O 4 , the power consumption at -40℃ and 160℃ increases significantly.

[0059] Figure 1 The figure is a curve diagram showing the power consumption of the manganese-zinc ferrite in Example 2 and Comparative Example 1 as a function of temperature. Figure 1 It can be seen that the power consumption of the manganese-zinc ferrite in Example 2 is low and does not change much in the range of -40°C to 160°C, while the loss of the manganese-zinc ferrite in Comparative Example 1 rises and deteriorates rapidly when the temperature is below 20°C and above 120°C in the range of -40°C to 160°C.

[0060] Comparative Example 2

[0061] The difference from Example 1 is that TiO 2 , the remaining steps are the same as in Example 1.

[0062] Comparative Example 3

[0063] The difference from Example 1 is that SnO 2 , the remaining steps are the same as in Example 1.

[0064] Comparative Example 4

[0065] The difference from Example 1 is that in step (4), the cooling stage is: in a mixed atmosphere of oxygen and nitrogen, the partial pressure of oxygen in the mixed atmosphere is 0.5%, and the temperature is cooled from 1260°C to room temperature at a rate of 3°C / min. The remaining steps are the same as in Example 1.

[0066] Comparative Example 5

[0067] The difference from Example 1 is that TiO 2 Replaced by SiO 2 , the remaining steps are the same as in Example 1.

[0068] Comparative Example 6

[0069] The difference from Example 1 is that SnO 2 Replace with Ta 2 O 5 , the remaining steps are the same as in Example 1.

[0070] Comparative Example 7

[0071] The difference from Example 1 is that Co 3 O 4 Replaced by Co 2 O 3 , the remaining steps are the same as in Example 1.

[0072] The properties of the manganese-zinc ferrite prepared in Comparative Examples 2-7 are shown in Table 2.

[0073] Table 2 Performance of manganese zinc ferrite prepared in Comparative Examples 2-7

[0074]

[0075] It can be seen from Table 2 that omitting TiO 2 or SnO 2 , the high-temperature power consumption of manganese-zinc ferrite will increase, and changing the atmosphere in the cooling stage will greatly increase both the low-temperature power consumption and the high-temperature power consumption of manganese-zinc ferrite. 2 Replaced by SiO 2 Or SnO 2 Replace with Ta 2 O 5 , the high and low temperature power consumption of manganese zinc ferrite will increase, and the Co 3 O 4 Replaced by Co 2 O3 , the high and low temperature power consumption of Mn-Zn ferrite will increase, this is because Co 2+ The ground state orbital momentum is non-zero, so there is a strong spin-orbit coupling effect, resulting in a very large positive magnetocrystalline anisotropy constant in spinel ferrites. 2+ The magnetocrystalline anisotropy constant K contributed by 1 The value decreases sharply with increasing temperature, so it is possible that there is a compensation point of K = 0 in the range below the Curie point, resulting in the second peak of the μ~T curve. 2+ Adding to iron-rich MnZn ferrite can significantly change the μ~T curve, Co 3 O 4 It contains cobalt in the +2 valence state, and Co 2 O 3 The valence state of the cobalt element in the body is +3, and it does not have this effect.

[0076] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. An ultra-wide temperature range and low-loss manganese-zinc ferrite with magnetic permeability, characterized in that: Including main ingredients and auxiliary materials; In terms of molar percentage, the main components include Fe2O3 53.48-53.78 mol%, ZnO 10.25-10.50 mol% and the balance MnO; The auxiliary materials include CaCO3, TiO2, Nb2O5, Co3O4 and SnO2.

2. The ultra-wide temperature and permeability low-loss manganese-zinc ferrite according to claim 1, characterized in that: Based on the total weight of the main components, the auxiliary materials include CaCO3 0.02-0.04%, TiO2 0.1-0.4%, Nb2O5 0.02-0.03%, Co3O4 0.3-0.5% and SnO2 0.1-0.3%.

3. The method for preparing the ultra-wide temperature-range permeability low-loss manganese-zinc ferrite according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Fe2O3, ZnO and MnO are weighed according to mole percentage, and then ball-milled and pre-calcined to obtain a pre-calcined material; (2) Weighing each auxiliary material according to the total weight of the main component, then ball-milling the auxiliary material and the pre-sintered material obtained in step (1), pressing and sintering to obtain the ultra-wide temperature range and low-loss manganese-zinc ferrite.

4. The preparation method according to claim 3, characterized in that: In step (1), the material-water ratio of the ball milling mixture is 1:(1.1-1.2), the material-ball ratio is 1:(3-4), the grinding balls are steel balls with a diameter of ф=3 mm, and the grinding time is 60-80 min.

5. The preparation method according to claim 3, characterized in that: In step (1), the pre-burning temperature is 930-960° C., and the feed rate is 2-4 kg / h; the spinel synthesis degree of the pre-burned material is 30-40%.

6. The preparation method according to claim 3, characterized in that: In step (2), the material-water ratio of the ball milling mixture is 1:(1-1.2), the material-ball ratio is 1:(5-6), the grinding balls are steel balls with a diameter of ф=3 mm, and the time is 70-90 min.

7. The preparation method according to claim 3, characterized in that: In step (2), zinc stearate is added during the compression molding process; the amount of zinc stearate added is 2-3‰.

8. The preparation method according to claim 3, characterized in that: In step (2), the sintering includes a heating stage, a heat preservation stage and a cooling stage.

9. The preparation method according to claim 8, characterized in that: The heating stage is: heating from room temperature to 1260-1300°C in an air atmosphere, and the heating time is 6-8h; the heat preservation stage is: heat preservation for 5-6h at 1260-1300°C and an oxygen content of 2-3%; the cooling stage is: cooling from 1260-1300°C to room temperature at a rate of 3-4°C / min in a reducing atmosphere.

10. Application of the ultra-wide temperature range, permeability and low loss manganese-zinc ferrite according to any one of claims 1 to 2 in transformers or inductors.

Citation Information

Patent Citations

  • Wide-temperature low-loss high-strength MnZn power ferrite, and preparation method and application thereof

    CN113956032A

  • Wide-temperature low-loss soft magnetic manganese zinc ferrite material suitable for 25-140 DEG C as well as preparation method and application of wide-temperature low-loss soft magnetic manganese zinc ferrite material

    CN116813323A

  • Wide-temperature wide-band magnetic manganese-zinc ferrite and preparation method thereof

    CN106278228A

  • Wide-temperature, high-frequency, low-loss and high-permeability manganese-zinc ferrite for LED and preparation method of manganese-zinc ferrite

    CN112592169A

  • Wide-temperature-range ultralow-power-consumption manganese-zinc ferrite material and preparation method thereof

    CN112707723A